Peran Pusat Pelaporan dan Analisis Transaksi Keuangan Dalam Mencegah Tindak Pidana Pencucian Uang di Lembaga Keuangan - Hayatun Nufus; Evi Deliana; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Today there are many modes or methods used in financial institutions to commit money laundering crimes, if this abuse continues it can harm the country's economy and perpetrators will continue to develop especially in using financial institutions to conduct money laundering. To realize a sound and stable financial system because of the importance of the role of the Financial Transaction Reports and Analysis Center (PPATK), which is an independent institution established in order to prevent and eradicate money laundering in accordance with Article 38 of Law No. 8 of 2010 Regulations concerning Eradication and Prevention of Money Laundering Crimes. The purpose of writing this essay is; First, to find out the role of the Financial Transaction Reports and Analysis Center (PPATK) in preventing money laundering in financial institutions; Second, to find out the countermeasures made by the Financial Transaction Reports and Analysis Center (PPATK) in preventing money laundering in financial institutions. The type of legal research used by the author is a type of normative legal research or library legal research. Normative legal research or library legal research.From the results of the study, there are two main things that can be concluded. First, the role of PPATK in preventing money laundering in financial institutions has been regulated in legislation such as Law No. 8 of 2010 concerning Prevention and Eradication of Money Laundering, Presidential Regulation and PPATK Head Regulation, where the role is in the implementation Procedures for Reporting Cash Financial Transactions, Suspicious Financial Transactions, Fund Transactions from Inside to Foreign Funds. There is a Temporary Termination and Postponement of Transactions, Integrated Service Provider Information System and Application of Principles of Knowing Service Users. Second, the countermeasures undertaken by the PPATK in preventing money laundering in financial institutions include efforts to maintain financial system stability, namely MER cooperation, PPATK Projections for the end of 2018 and its Final PPATK Reflections in 2018 by launching the Public Perception Index on Anti-Money Laundering and Eradication of Terrorism Funding, up to the receipt of financial transaction reports from Providers of Financial Services, and in efforts to overcome the collaboration between law enforcement and the Government.